FEDORA 2020-2023 - Chan, J; Erduran, S; Ioannidou, O (University of Oxford, 2023)
FEDORA, Future-oriented Science Education to enhance Responsibility and Engagement in the society of acceleration and uncertainty, is a 3-year EU-funded project. It started in September 2020 and deployed its activities until August 2023. It gathered 6 partner institutions from 5 European countries. The files “FEDORA_WP4” contain the dataset and research tools of Work Package 4, Toward a model for science education for the society of acceleration and uncertainty. The files contain questionnaire and interview data collected from student participants. The files “FEDORA_WP5” contain the dataset and research tools of Work Package 5, Recommendation for proactive and anticipatory policy making. The files include questionnaire data collected from WP5 participants. Details of the FEDORA project can be found at https://www.fedora-project.eu/